2015
DOI: 10.1159/000438577
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA MEG3 Inhibits Cell Proliferation and Induces Apoptosis in Prostate Cancer

Abstract: Background/Aims: Long non-coding RNAs (lncRNAs) play important roles in diverse biological processes, such as cell growth, apoptosis and migration. Although downregulation of lncRNA maternally expressed gene 3 (MEG3) has been identified in several cancers, little is known about its role in prostate cancer progression. The aim of this study was to detect MEG3 expression in clinical prostate cancer tissues, investigate its biological functions in the development of prostate cancer and the underlying mechanism. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
128
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(135 citation statements)
references
References 42 publications
6
128
0
Order By: Relevance
“…lncRNAs constitute a heterogeneous group of RNA molecules in eukaryotic cells and play a role in a wide variety of biological processes (Hanahan and Weinberg 2000). Previous studies have shown that expression of several lncRNAs is dysregulated in cancer tissues, such as MEG3 (Luo et al 2015), CCHE1 (Yang et al 2015), and HOTAIR (Ding et al 2015). In the present study, high levels of Loc554202 were observed in cervical cancer tissues compared with the surrounding non-tumor cervical tissues.…”
Section: Discussionsupporting
confidence: 51%
“…lncRNAs constitute a heterogeneous group of RNA molecules in eukaryotic cells and play a role in a wide variety of biological processes (Hanahan and Weinberg 2000). Previous studies have shown that expression of several lncRNAs is dysregulated in cancer tissues, such as MEG3 (Luo et al 2015), CCHE1 (Yang et al 2015), and HOTAIR (Ding et al 2015). In the present study, high levels of Loc554202 were observed in cervical cancer tissues compared with the surrounding non-tumor cervical tissues.…”
Section: Discussionsupporting
confidence: 51%
“…A total of 205 lncRNAs (Supplemental Tables S3 and S4) were identified in the stroma/epithelial compartments associated with the sigmoid colon and rectum. The stroma was particularly enriched in lncRNAs linked to cancer and embryogenesis, e.g., FENDRR (17a, 58) and MEG3 (34,38,61). Interestingly, with respect to sigmoidal and rectal tissue distribution, HOTAIRM1, a potential prognostic marker of colorectal cancer (32,51), was predominantly expressed in the rectum.…”
Section: Resultsmentioning
confidence: 99%
“…MEG3 is expressed in many human normal tissues, but has failed to express in a variety of human tumour cells, such as non-small cell lung cancer, bladder cancer, prostate cancer and other cancers (9)(10)(11)(12)(13)(14). Additionally, many studies have articulated that MEG3 gene plays an inhibiting role in various tumour cells (15)(16)(17)(18)(19)(20). However, the functional mechanism of MEG3 in MG63 has yet to be proven.…”
Section: Introductionmentioning
confidence: 99%